2022
DOI: 10.1063/5.0112223
|View full text |Cite
|
Sign up to set email alerts
|

New insights into the breathing physiology from transient respiratory nasal simulation

Abstract: We investigated the flow characteristics and heat transfer during nasal breathing in the complete human upper airway through the respiratory cycle using transient numerical simulations. We postulate the complete airway from the nasal cavity to the trachea most accurately represents dynamic airflow patterns during inhalation and exhalation as they are likely to be affected by downstream anatomical structures. We constructed a 3-Dimensional model from a healthy adult computed tomography (CT) scan. Computational … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 43 publications
2
18
0
Order By: Relevance
“…Due to the narrow passage connecting the paranasal sinuses with the nasal cavity, it is expected that negligible gas exchange takes place between the two [ 171 ]. This was supported by simulation results presented by Bradshaw et al [ 159 ]. Kaneda et al [ 126 ] reported that the inclusion of the paranasal sinuses did not improve the disagreement between computed and measured nasal resistances.…”
Section: Part I—computational Rhinologysupporting
confidence: 82%
See 2 more Smart Citations
“…Due to the narrow passage connecting the paranasal sinuses with the nasal cavity, it is expected that negligible gas exchange takes place between the two [ 171 ]. This was supported by simulation results presented by Bradshaw et al [ 159 ]. Kaneda et al [ 126 ] reported that the inclusion of the paranasal sinuses did not improve the disagreement between computed and measured nasal resistances.…”
Section: Part I—computational Rhinologysupporting
confidence: 82%
“…Furthermore, they observed that asymmetry in the respiratory cycle had little effect on the flow pattern in the nasal cavity compared to a sinusoidal inhalation/exhalation profile, which follows naturally from quasi-steady behavior. Bradshaw et al [ 159 ] highlighted several phenomena observed in their transient simulations that cannot be seen in steady flow. In particular, their results indicate that transient simulations of the entire breathing cycle are essential in order to correctly capture air conditioning via heating/cooling and humidification.…”
Section: Part I—computational Rhinologymentioning
confidence: 99%
See 1 more Smart Citation
“…The ND is a physiological variation of congestion and decongestion of the nasal mucosa of both the right and left nostrils over 30 min to several hours [3]. Nearly 80% of the healthy population shows a regular cycle [42].…”
Section: Discussionmentioning
confidence: 99%
“…A fundamental component of biological function is the rhythmic events ranging from subcellular elements to the entire organism. One such rhythm present in the nasal breathing of mammals is the nasal cycle [1][2][3][4]. The nasal cycle is the spontaneous congestion and decongestion of the nasal mucosa, where congestion of one side is accompanied by reciprocal decongestion of the contralateral side.…”
Section: Introductionmentioning
confidence: 99%